2018
DOI: 10.18632/aging.101560
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced longevity in budding yeast requires respiratory metabolism and glutathione recycling

Abstract: Heat-induced hormesis is a well-known conserved phenomenon in aging, traditionally attributed to the benefits conferred by increased amounts of heat shock (HS) proteins. Here we find that the key event for the HS-induced lifespan extension in budding yeast is the switch from glycolysis to respiratory metabolism. The resulting increase in reactive oxygen species activates the antioxidant response, supported by the redirection of glucose from glycolysis to the pentose phosphate pathway, increasing the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Interestingly, a switch from glycolysis to respiratory metabolism in yeast has been found to increase ROS production, activate the antioxidant response, and increase NADPH production, causing lifespan extension and hormesis response [48].…”
Section: Mitochondrial Damage In Agingmentioning
confidence: 99%
“…Interestingly, a switch from glycolysis to respiratory metabolism in yeast has been found to increase ROS production, activate the antioxidant response, and increase NADPH production, causing lifespan extension and hormesis response [48].…”
Section: Mitochondrial Damage In Agingmentioning
confidence: 99%
“…Since deletion of NADPH-generating enzymes in yeast generally led to increased longevity, a lifespan-extending signaling pathway appears to be activated by increased NADP + /NADPH. Other studies in yeast have shown that the heat shock-induced increase in replicative longevity was due to a transient increase in superoxide levels that signaled for the redirection of metabolic flux from glycolysis to the PPP to increase NADPH synthesis and GSH levels [197].…”
Section: Evidence For the Regulation Of Longevity By The Nadph-pomentioning
confidence: 99%
“…Moreover, proteostasis and metabolism are known to interact through pleiotropic mechanisms mediated by TORC1 and Hsp90 (Gopinath and Leu 2016;Perić et al 2017). Taken together, Dr. Krisko's work suggests that global metabolic reprogramming is required to achieve lifespan extension in yeast (Musa et al 2018).…”
Section: Proteostasis In Agingmentioning
confidence: 98%